Traditional Balinese Architecture as a Tourist Attraction in Bali: an Architect's Perspective - Paturusi, Syamsul Alam; Widiastuti, (ASTONJADRO, 2023)
The purpose of this research is to analyze the driving factors and inhibiting factors for the transformation of Balinese Traditional Architecture (ATB) designs in tourism facilities in Denpasar and Badung. Through a questionnaire as many as 48 samples from Architects working in Denpasar and Badung were analyzed through IFAS and EFAS and the Internal External Matrix, the general positions and strategies were obtained. The results of the study show that the main strength of internal factors is the existence of Provincial and Denpasar Regional Regulations regarding building layout which is a very meaningful back-up for implementing Balinese-style designs in tourist facilities. Meanwhile, the main driving factor from external factors is the development of tourism in Bali which is quite large. In this way, in the future, a mutually beneficial relationship will be created between Balinese Architecture and Tourism.